Progress of Rice Improvement through Recurrent Selection - Buang Abdullah (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
Improved rice varieties play an important role in increasing rice production, through raising and/or stabilizing rice productivity. Thus, it is urgent to develop improved rice varieties. Selection method is an important step in rice improvement. Implementation of recurrent selection in rice improvement was aimed to increase the efficiency and insurance in the success of improvement. Since 2004, Indonesian Institute for Rice Research has applied recurrent selection in breeding program. Promising lines of earliness and high yield potential were developed in relatively short time. A number of advanced lines has been produced and will be further evaluated, and a number of populations has been selected and used as base populations for recurrent selection in rice improvement program. Key words: breeding, earliness, high yield rice, improvement